A Gaussia luciferase cell-based system to assess the infection of cell culture- and serum-derived hepatitis C virus. - George Koutsoudakis (Public Library of Science (PLoS), 2012)
Robust replication of hepatitis C virus (HCV) in cell culture occurs only with the JFH-1 (genotype 2a) recombinant genome. The aim of this study was to develop a system for HCV infection quantification analysis and apply it for the selection of patient sera that may contain cell culture infectious viruses, particularly of the most clinically important genotype 1. Initially, a hepatoma cell line (designated Huh-7.5/EG(4A/4B)GLuc) was generated that stably expressed the enhanced green fluorescent protein (EGFP) fused in-frame to the secreted Gaussia luciferase via a recognition sequence of the viral NS3/4A protease. Upon HCV infection, NS3/4A cleaved at its signal and the Gaussia was secreted to the culture medium, thus facilitating the infection quantification. The Huh-7.5/EG(4A/4B)GLuc cell line provided a rapid and highly sensitive quantification of HCV infection in cell culture using JFH-1-derived viruses. Furthermore, the Huh-7.5/EG(4A/4B)GLuc cells were also shown to be a suitable host for the discovery of anti-HCV inhibitors by using known compounds that target distinct stages of the HCV life cycle; the Ź-factor of this assay ranged from 0.72 to 0.75. Additionally, eighty-six sera derived from HCV genotype 1b infected liver transplant recipients were screened for their in vitro infection and replication potential. Approximately 12% of the sera contained in vitro replication-competent viruses, as deduced by the Gaussia signal, real time quantitative PCR, immunofluorescence and capsid protein secretion. We conclude that the Huh-7.5/EG(4A/4B)GLuc cell line is an excellent system not only for the screening of in vitro replication-competent serum-derived viruses, but also for the subsequent cloning of recombinant isolates. Additionally, it can be utilized for high-throughput screening of antiviral compounds.